Trans‐oral robotic assisted tongue base mucosectomy for investigation of cancer of unknown primary in the head and neck region. The UK experience. (26th March 2017) - Winter, S.C.; Ofo, E.; Meikle, D.; Silva, P.; Fraser, L.; O'Hara, J.; Kim, D.; Robinson, M.; Paleri, V.
Abstract: Objectives: The diagnosis of cancer of unknown primary (CUP) in head and neck occurs when the treating clinicians have utilised all available diagnostic tests and failed to identify the origin of the disease. There is no agreed consensus on which diagnostic investigations to use, or the order in which to use them in, although broad recommendations exist. Small tumours arising in the tongue base can be below the limits of resolution of conventional diagnostic techniques. Given the difficulty in targeting the tongue base, current practice involves blind random biopsies, which leads to a variable detection rate. Robotically assisted surgical removal of the tongue base, tongue base mucosectomy (TBM) has been shown to improve diagnostic yield. This study reports the diagnostic hit rate for tongue base primaries using this technique. Design: Retrospective case review. Setting: UK Head and Neck Centres. Participants: Patients presenting as an unknown primary, investigated with clinical examination, PET‐CT and palatine tonsillectomy. Main Outcome Measures: The detection of a primary site of head and neck cancer in the otherwise unknown primary tumour. Results: The primary tumour site was identified in the tongue base in 53% (n=17) of patients. In 15 patients the tumour was in the ipsliateral tongue base (88%) while in two cases (12%) the tumour was located in contra lateral tongue base. Conclusions: Trans‐oral robotic assisted TBM raises the possibility of identifying over 50% of tumours that would otherwise be classified as CUP. Identifying these in the contralateral tongue base has implications for treatment planning and outcome.